PROBLEMATIKA MINORITAS MUSLIM DI KANADA DAN PERANCIS - Afadlal, Afadlal (Pusat Penelitian Politik, 2007)
In this summary the research on the problem of Moslem minority in Canada and France is to describe how Moslem as minority in western country affected by state and social bias after 9111 Tragedy Interaction between Moslem as minority and immigrant community and white people community in western country has long been biased withprejudice and intolerance This research is to describe how differences between those two communities have brought about an indecisive integration restrained cultural assimilation Bringing the gap between two different communities has become the major concern but the result is a long way to come The main problem of integration Moslem community in western country is strong alienation oflslamic value by white people in western community For Moslem community in Canada and France there is also a growing inclination toward divergence in coping with western culture For western community the causes are strong ethnocentrisms and nativity ofwhite people that comefrom a feeling ofcultural supremacies Thosefactors have constrained new socialformation in western community.